Molecular epidemiology of rotavirus a among clinical isolates at a hospital in bangkok, thailand (2016-2017) - Nopbhawan Na Rangsee (2022)
Rotavirus group A (RVA) is the major cause of acute diarrhea in children under 5 years of age. As viral genotypic distribution changes over time, prevalence, genotype and antigenic site of RVA were determined in stool samples collected at Siriraj Hospital, Mahidol University, Bangkok, Thailand during 2016-2017. Prevalence of RVA was 12.3%, highest among children 0-6 months of age (42%) and 1-2 years of age (34%) in 2016 and 2017 respectively; peak of infection was from February to April; six genotypes were found, 89% being G3P[8]; antigenic site comparison of VP4 and VP7 proteins showed highest number of amino acid substitutions at 8-1 and 8-3 epitopes in VP4 protein, and 7-1b epitope in VP7 protein compared to two vaccine strains; and phylogenetic analysis revealed VP4 genes clustering into P8 and P4 gen-otypes, and VP7 genes into G2, G3, and G9 genotypes. There is no significant difference between RVA genotype and patient demographics. Vomiting and dehydration were associated (although weakly significant due to low number of patients) with G2P[8] or G8P[8] strain infection. This study indicates the genotypic distribution changes over times. Comparison of amino acid at the antigenic sites between circulating strains and vaccine strains showed several amino acid differences.